Extracellular Vesicles Promote the Formation of Pre-Metastasis Niche in Gastric Cancer - Tang, Diya; Liu, Shanshan; Shen, Hong; Deng, Gongping; Zeng, Shan (Frontiers in Immunology, 2022)
Globally, gastric cancer (GC) ranks fourth in the incidence of malignant tumors. The early clinical manifestations of GC lack specificity. Most patients are already at an advanced stage when they are first diagnosed, and their late progression is mainly due to peritoneal metastasis. A pre-metastatic microenvironment is formed, before the macroscopic tumor metastasis. Extracellular vesicles (EVs) are nanovesicles released by cells into body fluids. Recent studies have shown that extracellular vesicles can affect tumor microenvironment by carrying cargo to participate in cell-to-cell communication. EVs derived from gastric tumor cells mediate the regulation of the pre-metastasis niche, and act as a coordinator between tumor cells and normal stroma, immune cells, inflammatory cells and tumor fibroblasts to promote tumor growth progress and transfer. This review highlights the regulatory role of EVs in the pre-metastatic niche of GC and mulls EVs as a potential biomarker for liquid biopsy.